Industrial Assessment for the Exposed Carbonate Rocks on Safeen Mountain Kurdistan Region of Iraq - Varoujan Sissakian; Ala Ghafour (Iraqi Geological Journal, 2024)
The Safeen Mountain is one of the main mountains in the Iraqi Kurdistan Region, it forms one of the long anticlines trending NW – SE. The exposed formations on the top of the mountain are Qamchuqa, Bekhme, and Shiranish, with carbonate rocks of different types and thicknesses. Sampling took place in the exposed rocks on the top of the mountain where a road crosses the mountain, and a total of 20 samples out of 84 m thickness of the outcrop were collected. The distance between sampling intervals was depending on the lithological variation of the bedrock and each sample was collected to represent the sampling interval. The samples were subjected to XRF to indicate the main oxides percentages in each sample. The acquired results from the XRF showed the studied rocks can be used for cement and paper industries based on Iraqi Standards. They can also be considered using it in the sugar industry after a slight modification as well as in the drug industry.